The United Nations a Myth of Human rights with reference to the injunctions of Islam - Nadeem, Amir; Bhatti, Dr. Shaukat Hussain (Al-Irfan, 2022)
Abstract: - Human Rights’ history is as old as the human himself is. When we look into the origin of human rights, it appears lucid that with the Creation of Mankind, Allah Almighty has bestowed some rights on His Supreme Creature. Therefore, the discussion on the subject is not new. Fundamental Rights as well as an appraisal on the topic, a misconception always haunts the mind that the origin of human rights has been detailed in the 19th century when the United Nations came into existence on 26th June 1945. This paper illuminates that the myth regarding human rights is based on the Universal Declaration of Human Rights (UDHR) adopted by the United Nations General Assembly Session held on 10th December 1948 in France after World War II. First time in the history of mankind, an organized and well-integrated effort has been made to recognize human rights worldwide and almost every nation in the world realizes the sensitivity of this issue. On the other hand, when we take stock of the last Sermon of Hazrat Muhammad (SAW), delivered on 10 A.H. (623AD) in Makkah, it was the first-ever Human Right Charter. This article reveals that it is not the West (United Nations) that introduced the human laws for the welfare of humanity rather this is Allah Almighty who has given the human rights attached with some responsibilities to be performed with the creation of the human race on this planet. This paper paves the way to give an overall view of this reality by removing the myth/ illusion that it is the United Nations that chanted human rights. I seek to take this sensitive issue keeping in view the prevalent scenario of the West which raised voices against Islam on one pretext or the other. The prime objective of this article is to unfurl the riddle of this United Nations’ myth and to solidify the notion that Muhammad (SAW) in his last sermon had given the postmodern code of human rights. Keys words: - international law, Islamic law, United Nations, Domestic law, Human Rights